Giving Vaccines in Coping With Covid-19 in the Poly Room of the Otanaha Hospital, Gorontalo City - Rini Asnawati; Sabirin B. Syukur; Ramiyatullah R. Hurudji; Bahtiar Manumba (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
The purpose of this study is to increase public knowledge, especially people who visit the Poli Room of the Otanaha Hospital, Gorontalo City about administering vaccines in the fight against COVID-19. Vaccination is an absolute thing that must be a concern for all elements of society as the vanguard in an effort to break the chain of transmission of COVID-19. Corona virus 2019 or covid-19 is a pandemic that has resulted in high mortality rates in various parts of the world. Knowledge of the good covid-19 pandemic and clean and healthy living behavior as an effort to prevent the transmission of covid-19 is important to apply. the public regarding the provision of vaccines in dealing with covid-19 and community behavior during the covid-19 pandemic. The research design used pretest-posttest. The research sample amounted to 20 respondents. Community Service (Counseling) is carried out 1 time in 2 weeks, the assessment of increasing knowledge before and after treatment using the descriptive statistical test obtained results at the pre-test with 70% good category, 15% enough and 10% less good and the posttest results with good category 80% and sufficient category 20%. Based on the results of the training, it showed that most of the students stated that this training was very useful because they gained knowledge and understanding of. The results of the study there was an increase in knowledge before and after counseling, Conclusion: there was an increase in knowledge after counseling about administering vaccines in the prevention of covid-19